(untitled) (INNOVATIVE ECONOMY, 2020)
Cherkas N.I. CHALLENGES OF INTERNATIONAL COMPETITIVENESS IN GLOBAL NETWORKS UNDER THE CONDITIONS OF HYPER-GLOBALIZATION Purpose. The study aims to perform a systematic analysis of the main challenges of the countries’ competitiveness and their participation in global production networks under the conditions of hyper-globalization. Methodology of research. The following scientific methods were applied: the historical-logical method (analyzing the changes of globalization in the 20th and 21st centuries), methods of analysis (studying the dynamics of global flows), system analysis (research of the structure of global corporate profits), induction, deduction and synthesis (in substantiating international competitiveness challenges). Findings. The paper analyzes the main features of globalization in the 20th century and hyper-globalization in the 21th century. We examine the dynamics of world exports of goods, services and foreign direct investment, which allowed to determine the tendencies of trade flows slowdown due to the shorter supply chains. The structure of global corporate profit is analyzed, which is largely determined by the participation of companies in global networks. The main challenges that determine the trends of global networks and value chains under the conditions of hyper-globalization are explained in detail: industrial revolution (digital innovations and sustainable growth); innovation reversal and mass customization; development of micro-multinationals; the speed and accessibility of trade; liberalization. The future research directions suppose an empirical analysis of the international competitiveness’s factors, taking into account the influence of global production and trade networks. Originality. The main challenges of competitiveness, determined by participation in global production networks and value chains, are formulated and substantiated. Practical value. The research results address the problems of effective enterprises’ integration into global networks and value chains and their competitiveness increase. Considering the main challenges of hyper-globalization will contribute to the development of competitive internationalization strategies of domestic companies. Key words: hyper-globalization; competitiveness; global networking; value chains.